Examining the Feedback Response of Residential Electricity Consumption towards Changes in its determinants: Evidence from Malaysia - Ivy-Yap, Lee Lian; Bekhet, Hussain Ali (International Journal of Energy Economics and Policy, 2015)
Residential electricity consumption in Malaysia is increasing rapidly and poses a threat to energy security. Therefore, it is very important to understand the way residential electricity consumption responds to its determinants so that effective measures to contain its rapid growth can be undertaken. The current study aims to examine the responsiveness of residential electricity consumption towards real disposable income, price of electricity, price of electrical appliances population and foreign direct investment in Malaysia for 1978-2013 period. Residential electricity consumption is only elastic towards real disposable income. The magnitude of own price elasticity is larger than cross elasticity of complements. The study shed some light on the responsiveness of residential electricity consumption, which can help Malaysia in developing new policies to control energy consumption without affecting economic growth adversely. Keywords: residential electricity consumption; complements; co-integration; elasticities; Malaysia. JEL Classifications: C32; N7; Q41; Q48